Decolonizing feminism: Challenging connections between settler colonialism and heteropatriarchy - Arvin, Maile; Tuck, Eve; Morrill, Angie (Feminist Formations, 2013)
The article explores two intertwined ideas: that the United States is a settler colonial nation-state and that settler colonialism has been and continues to be a gendered process. The article engages Native feminist theories to excavate the deep connections between settler colonialism and heteropatriarchy, highlighting five central challenges that Native feminist theories pose to gender and women's studies. From problematizing settler colonialism and its intersections to questioning academic participation in Indigenous dispossession, responding to these challenges requires a significant departure from how gender and women's studies is regularly understood and taught. Too often, the consideration of Indigenous peoples remains rooted in understanding colonialism as an historical point in time away from which our society has progressed. Centering settler colonialism within gender and women's studies instead exposes the still-existing structure of settler colonialism and its powerful effects on Indigenous peoples and settlers. Taking as its audience practitioners of both "whitestream" and other feminisms and writing in conversation with a long history of Native feminist theorizing, the article offers critical suggestions for the meaningful engagement of Native feminisms. Overall, it aims to persuade readers that attending to the links between heteropatriarchy and settler colonialism is intellectually and politically imperative for all peoples living within settler colonial contexts.
https://www.feministformations.org
Keywords: OFDIG; amériques; approches et analyses; colonialisme; féminisme autochtone; féminisme décolonial; intersectionnalité; militance; patriarcat; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Sakahàn: art indigène international - Hill, Greg A.; Hopkins, Candice; Lalonde, Christine; Musée des beaux-arts du Canada (Musée des beaux-arts du Canada, 2013)
Sakahàn, qui veut dire « allumer [un feu] » en algonquin, réunit plus de 150 œuvres récentes créées par 80 artistes provenant de 16 pays, y compris des installations conçues spécialement pour ce projet. Poétiques, surprenantes et audacieuses, ces œuvres proposeront une relecture des enjeux culturels et sociaux auxquels font face les peuples autochtones. Des sites partenaires dans la région d’Ottawa et à l’étranger participeront à cet événement culturel sans précédent.
Keywords: approches et analyses; arts; arts autochtones; arts visuels et médiatiques; cours; discipline; féminisme autochtone; har4600; histoire de l'art; premier cycle

Towards an Australian Indigenous Women's Standpoint Theory - Moreton-Robinson, Aileen (Australian feminist studies, 2013)
In this article I outline an Australian Indigenous women's standpoint theory. I argue that an Indigenous women's standpoint generates problematics informed by our knowledges and experiences. Acknowledging that Indigenous women's individual experiences will differ due to intersecting oppressions produced under social, political, historical and material conditions that we share consciously or unconsciously. These conditions and the sets of complex relations that discursively constitute us in the everyday are also complicated by our respective cultural differences and the simultaneity of our compliance and resistance as Indigenous sovereign female subjects.
Donné en lecture au cours POL4212. https://www-tandfonline-com.proxy.bibliotheques.uqam.ca/doi/full/10.1080/08164649.2013.876664
Keywords: approches et analyses; australie; cours; droits des femmes*; féminisme autochtone; histoire et politique; intersectionnalité; point de vue situé; pol4212; premier cycle; ressource en ligne; régions géographiques; thématiques

Ethical waters: Reflections on the healing walk in the tar sands - Wong, Rita (Feminist Review, 2013)
Keywords: activisme; amériques; approches et analyses; autochtones; canada; cours; fem1000; féminisme autochtone; guérison; militance; premier cycle; ressource en ligne; régions géographiques; santé; thématiques